Luminescent twelve-nuclear rhenium clusters. Issue 33 (31st July 2019) - Gayfulin, Yakov M.; Brylev, Konstantin A.; Ryzhikov, Maxim R.; Samsonenko, Denis G.; Kitamura, Noboru; Mironov, Yuri V.
Abstract : A series of bioctahedral rhenium cluster compounds demonstrate red luminescence in both the solid phase and solution. Abstract : The first luminescent twelve-nuclear rhenium cluster complexes were obtained. Three new clusters, namely, [Re12 CS14 (μ-Cl)3 Cl6 ] 5−, [Re12 CS14 (μ-Br)3 Cl6 ] 5− and [Re12 CS14 (μ-Br)3 Br6 ] 5−, were synthesized using the non-isovalent substitution of μ-O ligands within the Re12 CS14 (μ-O)3 0 cluster core by halide anions. The geometry of the new clusters was investigated by X-ray structural analysis, and the electronic structures were evaluated by the use of DFT calculations. It was found that compounds based on these anions showed red luminescence in both the solid state and solution that was never observed before for previously studied twelve-nuclear rhenium clusters.